2012
DOI: 10.1007/s12603-012-0072-6
|View full text |Cite|
|
Sign up to set email alerts
|

Glomerular filtration rate estimated by Cockcroft-Gault formula better predicts anti-Xa levels than modification of the diet in renal disease equation in older patients with prophylactic enoxaparin

Abstract: In hospitalized patients older than 65 years old, the Cockcroft-Gault equation, in contrast to the MDRD equation, is able to predict the risk of higher anti-Xa levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
2
1
5
Order By: Relevance
“…The characteristics of our dalteparin and unfractionated groups were grossly similar, but had key differences, such as female predominance in the LMWH group; but, given that relatively higher anti factor Xa levels have been associated with LMWH in females, this again should not have biased the results significantly. 28,31,32 In conclusion, contrary to previous studies that seemed to suggest a higher risk of bleeding associated with LMWH in those with renal insufficiency, our retrospective study showed that the LMWH dalteparin at therapeutic doses does not result in increased instances of clinically significant hemorrhage. Our findings serve as convincing evidence that increased safety concerns for dalteparin use may not be warranted, and therefore the ease of use and steady pharmacokinetics for LMWH may make this therapy preferred over the frequent monitoring of aPTT and the inherent flaws of unpredictable pharmacokinetics for UFH.…”
Section: Discussioncontrasting
confidence: 94%
“…The characteristics of our dalteparin and unfractionated groups were grossly similar, but had key differences, such as female predominance in the LMWH group; but, given that relatively higher anti factor Xa levels have been associated with LMWH in females, this again should not have biased the results significantly. 28,31,32 In conclusion, contrary to previous studies that seemed to suggest a higher risk of bleeding associated with LMWH in those with renal insufficiency, our retrospective study showed that the LMWH dalteparin at therapeutic doses does not result in increased instances of clinically significant hemorrhage. Our findings serve as convincing evidence that increased safety concerns for dalteparin use may not be warranted, and therefore the ease of use and steady pharmacokinetics for LMWH may make this therapy preferred over the frequent monitoring of aPTT and the inherent flaws of unpredictable pharmacokinetics for UFH.…”
Section: Discussioncontrasting
confidence: 94%
“…Ceci peut être un avantage au niveau pharmacociné tique car le poids est une estimation du volume de distribution du mé dicament qui intervient né cessairement dans la pharmacociné tique [48]. Ceci pourrait expliquer que la formule de Cockcroft donne de meilleurs ré sultats dans certaines é tudes de pharmacociné tique et soit encore pré fé ré e par certains auteurs [49]. Ainsi, une é tude française fré quemment cité e retrouve une corré lation entre les concentrations de facteur Xa et la formule de Cockcroft chez des patients traité s par hé parine de bas poids molé culaire, alors qu'aucune corré lation n'est retrouvé e avec la formule MDRD [49].…”
Section: L'estimation Du Dfg : Rappels Statistiquesunclassified
“…Ceci pourrait expliquer que la formule de Cockcroft donne de meilleurs ré sultats dans certaines é tudes de pharmacociné tique et soit encore pré fé ré e par certains auteurs [49]. Ainsi, une é tude française fré quemment cité e retrouve une corré lation entre les concentrations de facteur Xa et la formule de Cockcroft chez des patients traité s par hé parine de bas poids molé culaire, alors qu'aucune corré lation n'est retrouvé e avec la formule MDRD [49]. Notons que ces corré lations ne sont pas retrouvé es par d'autres [50], et que, par ailleurs, ce type d'argumentaire n'est que trè s indirect pour pouvoir favoriser une é quation par rapport à une autre.…”
Section: L'estimation Du Dfg : Rappels Statistiquesunclassified
See 2 more Smart Citations